الإدارة المحلية وتحديات المشاركة دراسة حالة لواقع المشاركة السياسية في وحدات الإدارة المحلية بمدينة بنغازي - امنينة عبير إبراهيم (Scientific Journal of University of Benghazi, 2020)
The study aims to identify political participation in localities, and the most important challenges associated with this participation. Also, the research interest to find out the ability of the political system to motivate the citizens to participate in politics. The study covered a number of axes, namely: The most important legislation and procedures organizing the political participation process in localities. The electoral process for local units, to determine the nature of citizen participation The procedures regulating the participation of civil society in decisions' making at the local level. The study concluded that, the civil society should be made aware of participation in the decision-making process, to achieve democracy at the local level, and play an active role in local participation in decision-making..